Mental fatigue and ball sports: a narrative review focused on physical, technical, and tactical performance - Yago Pessoa da Costa; Carlos Freitas-Júnior; Dalton de Lima-Júnior; Elizabeth Lourdes Soares-Silva; Gilmário Ricarte Batista; Lawrence Hayes; Leonardo de Sousa Fortes (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: This narrative review aimed to explore the effect of mental fatigue on physical, technical, and tactical performance in ball sports. Methods: Three Databases, PUBMED, SCOPUS, and SCIELO, were used to search for a scientific publication. The criterions adopted were: a) published in a peer-reviewed journal; b) adopted at least one manipulation check related to mental fatigue; c) mental fatigue induced by a cognitive task before the outcome task, and d) study participants were ball sports athletes. Result: The quality of this narrative review was rated at 11 (SANRA scale 0-12), and the papers analyzed were published between 2015 and 2022. Twenty-one experimental studies were included in this review. Most studies were in invasion sports (n = 13; 72%), and non-ecological tasks were used to induce mental fatigue (n = 15; 83%). Regarding performance in endurance tests, mentally fatigued athletes had performance impaired. However, when assessed during a small-sided or simulated game, data were inconclusive within the literature. Moreover, athletes presented attenuated perceptual skills (e.g., visual field). Consequently, this worsened motor skills, technical-tactical performances, and tactical behavior. Conclusions: Cognitively demanding tasks should be avoided before training and sports competitions because they can lead the athlete to mental fatigue and impair performance. This impairment is identified in physical performance (endurance tasks) and technical and tactical performance. Finally, it is recommended that athletes do not perform tasks that cause mental fatigue 2 h before the sports event.